Analisis Dampak Pemanfaatan Teknologi Digital terhadap Keberhasilan Pembelajaran dengan Menggunakan Model Pembelajaran Terbalik di Pendidikan Tinggi : Penelitian - Budimansyah Purba, Arif; Jajang Mulyana; Ahmad Mubarok; Wawan Kusdiawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the impact of digital technology utilization on learning success in higher education using the flipped learning model. The flipped learning model shifts content delivery outside the classroom through digital media, allowing in-class time to be focused on active discussions and problem-solving. This research uses a quantitative approach with a survey method involving students from various study programs at a higher education institution. Data were collected through questionnaires measuring students' perceptions of the effectiveness of digital technology, participation levels, and learning outcomes. The analysis results indicate that the use of digital technology significantly enhances student engagement and understanding of the material, positively impacting learning success. These findings highlight the importance of integrating technology into innovative learning strategies to support the transformation of higher education.